2008
DOI: 10.1534/genetics.107.083881
|View full text |Cite
|
Sign up to set email alerts
|

Semidominant Mutations in Reduced Epidermal Fluorescence 4 Reduce Phenylpropanoid Content in Arabidopsis

Abstract: Plants synthesize an array of natural products that play diverse roles in growth, development, and defense. The plant-specific phenylpropanoid metabolic pathway produces as some of its major products flavonoids, monolignols, and hydroxycinnamic-acid conjugates. The reduced epidermal fluorescence 4 (ref4) mutant is partially dwarfed and accumulates reduced quantities of all phenylpropanoid-pathway end products. Further, plants heterozygous for ref4 exhibit intermediate growth and phenylpropanoid-related phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 85 publications
3
44
0
Order By: Relevance
“…whereas mutants lacking MED5a and MED5b accumulate elevated levels of HCEs and HCE:hydroxycinnamyl alcohol coupling products (Stout et al, 2008;Bonawitz et al, 2012). We have also recently shown that disruption of MED5a and MED5b restores lignin biosynthesis and growth of the C39H-deficient ref8 mutant (Bonawitz et al, 2014), demonstrating a role for Mediator in repressing lignin biosynthesis in response to a metabolic block in the phenylpropanoid pathway.…”
mentioning
confidence: 71%
“…whereas mutants lacking MED5a and MED5b accumulate elevated levels of HCEs and HCE:hydroxycinnamyl alcohol coupling products (Stout et al, 2008;Bonawitz et al, 2012). We have also recently shown that disruption of MED5a and MED5b restores lignin biosynthesis and growth of the C39H-deficient ref8 mutant (Bonawitz et al, 2014), demonstrating a role for Mediator in repressing lignin biosynthesis in response to a metabolic block in the phenylpropanoid pathway.…”
mentioning
confidence: 71%
“…In addition, two of the Arabidopsis Med33 subunits (AT2G48110 and AT3G23590; Bäckströ m et al, 2007) are annotated as REDUCED EPIDERMAL FLUORESCENCE4 (REF4) and REF4-RELATED1, respectively (The Arabidopsis Information Resource [TAIR]). The dominant mutations in REF4 lead to reduced accumulation of phenylpropanoid end products and affect plant growth Stout et al, 2008). Although the exact function of REF4 has not been ascertained, the authors argue against the function of REF4 as a TF, owing to putative membranespanning domains in the protein.…”
Section: Identification Of Med Proteins In Plantsmentioning
confidence: 99%
“…Although the exact function of REF4 has not been ascertained, the authors argue against the function of REF4 as a TF, owing to putative membranespanning domains in the protein. However, REF4 is not a part of any membrane proteome (Stout et al, 2008;TAIR) and has been isolated as a component of the Med complex in a biochemical screen (Bäckströ m et al, 2007), making it a legitimate transcriptional regulator. On the other hand, the rice counterparts of Med5/33 have been annotated as "structural constituent of ribosome" in the Rice Genome Annotation Project (RGAP) database.…”
Section: Identification Of Med Proteins In Plantsmentioning
confidence: 99%
“…Wild-type Arabidopsis plants appear blue under UV light due to the presence of sinapoylmalate, a UV fluorescent secondary metabolite that is accumulated in the adaxial leaf epidermis. Sinapoylmalate is synthesized from phenylalanine via the phenylpropanoid pathway, and several biosynthetic enzymes and regulatory components with key roles in this biosynthetic pathway have been identified through the analysis of ref mutants (Ruegger and Chapple, 2001;Franke et al, 2002;Stout et al, 2008;Schilmiller et al, 2009). Surprisingly, despite the fact that it was first isolated based upon its phenylpropanoid metabolism defect, the identification of REF2 showed that the mutant is defective in the gene encoding CYP83A1, the enzyme that catalyzes the aldoxime-metabolizing step in aliphatic glucosinolate biosynthesis (Hemm et al, 2003).…”
Section: Introductionmentioning
confidence: 99%